2019
DOI: 10.1111/cup.13439
|View full text |Cite
|
Sign up to set email alerts
|

Lichenoid folliculitis of the scalp in four patients with ichthyosiform skin disorders and cicatricial alopecia

Abstract: Ichthyosis is a heterogeneous group of inherited skin disorders characterized by a defect of keratinization. Patients diagnosed with lamellar ichthyosis (LI) and some ichthyosiform syndromes, such as the Conradi-Hünermann-Happle syndrome (CHHS), usually present with hair loss. Even though only few dermatologic complaints carry as many emotional overtones as hair loss, there are very few data available in the literature regarding scalp histopathological features in ichthyosis. A better understanding of scalp ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…A histological study of the scalp in another case of CHH 11 revealed pseudopelade with fibrous cords reaching the epidermis, orphaned hair muscles, and lack of normal hair follicles. On the trichoscopic examination, reports have described hair shafts that may be uneven in diameter, loss of follicular openings, peripilar casts, polytrichia, fractured hair, transparent proximal hair shaft emergences, trichorrhexis nodosa, pili torti, anisotrichia, broken hair, and inter and perifollicular desquamation 17 . Several of these findings correlate with trichoscopic features of cicatricial alopecia.…”
Section: Discussionmentioning
confidence: 98%
“…A histological study of the scalp in another case of CHH 11 revealed pseudopelade with fibrous cords reaching the epidermis, orphaned hair muscles, and lack of normal hair follicles. On the trichoscopic examination, reports have described hair shafts that may be uneven in diameter, loss of follicular openings, peripilar casts, polytrichia, fractured hair, transparent proximal hair shaft emergences, trichorrhexis nodosa, pili torti, anisotrichia, broken hair, and inter and perifollicular desquamation 17 . Several of these findings correlate with trichoscopic features of cicatricial alopecia.…”
Section: Discussionmentioning
confidence: 98%
“…These ulcerations may be linked to skin barrier anomalies responsible for abnormal inflammatory processes and disturbed microflora. Gene mutations may also be responsible for the selective expression of antigenic proteins by hair follicles ( 3 ). Other contributory factors cannot be ruled out: repeated trauma/maceration secondary to wearing a wig or scarf and pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…This stereotypical pattern seen in ARCI due to TGM1 mutations has not yet been described, even if present on a clinical photograph provided in the series by Putterman, 3 or in patients without molecular diagnosis. 4,5 The fact that only patients with variants in TGM1 or ABCA12 (along with HI) have alopecia may help for suspecting the causal gene before molecular testing and is therefore relevant for prognosis. We cannot exclude the fact that some patients had additional mutations in genes associated with hair loss (such as ST14), thus representing a limitation of our study.…”
mentioning
confidence: 99%
“…Regarding pathophysiology, skin inflammation, together with a disturbed intrafollicular microflora, could contribute to this ARCI-related alopecia. 5 A bigger prospective study, combining clinical data, genomics, proteomics and microbiome would better explain this scaring alopecia and help to identify new therapeutical approaches, ideally at early stages, to prevent irreversible lesions.…”
mentioning
confidence: 99%